2009
DOI: 10.1017/s003118200900554x
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma caninum n. sp. (Protozoa: Kinetoplastida) isolated from intact skin of a domestic dog (Canis familiaris) captured in Rio de Janeiro, Brazil

Abstract: An unknown Trypanosoma species was isolated from an axenic culture of intact skin from a domestic dog captured in Rio de Janeiro, Brazil, which was co-infected with Leishmania (Viannia) braziliensis. Giemsa-stained smears of cultures grown in different media revealed the presence of epimastigotes, trypomastigotes, spheromastigotes, transitional stages, and dividing forms (epimastigotes or spheromastigotes). The highest frequency of trypomastigotes was observed in RPMI (15.2%) and DMEM (9.2%) media containing 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
42
0
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 32 publications
7
42
0
3
Order By: Relevance
“…These animals are of particular interest with regard to the transmission cycle of Leishmania chagasi and Trypanosoma cruzi, because they are considered reservoirs for both agents and enhancers of transmission in the peridomicile, and consequently a risk factor for the human population (3) (4) . Trypanosoma caninum is the most recently described species of the Trypanosoma genus affecting dogs (5) , with 53 cases confirmed in different regions of Brazil (6) prior to this present study. The species has unique biological characteristics, including its isolation exclusively from intact skin fragments (5) (7) and the presence of afl agellate epimastigote forms in axenic cultures (8) .…”
Section: Domestic Dogs Are Naturally Infected With Different Species supporting
confidence: 60%
See 1 more Smart Citation
“…These animals are of particular interest with regard to the transmission cycle of Leishmania chagasi and Trypanosoma cruzi, because they are considered reservoirs for both agents and enhancers of transmission in the peridomicile, and consequently a risk factor for the human population (3) (4) . Trypanosoma caninum is the most recently described species of the Trypanosoma genus affecting dogs (5) , with 53 cases confirmed in different regions of Brazil (6) prior to this present study. The species has unique biological characteristics, including its isolation exclusively from intact skin fragments (5) (7) and the presence of afl agellate epimastigote forms in axenic cultures (8) .…”
Section: Domestic Dogs Are Naturally Infected With Different Species supporting
confidence: 60%
“…Trypanosoma caninum is the most recently described species of the Trypanosoma genus affecting dogs (5) , with 53 cases confirmed in different regions of Brazil (6) prior to this present study. The species has unique biological characteristics, including its isolation exclusively from intact skin fragments (5) (7) and the presence of afl agellate epimastigote forms in axenic cultures (8) . It appears to be nonpathogenic to dogs, in which the infection triggers a mild humoral immune response (7) (9) .…”
Section: Domestic Dogs Are Naturally Infected With Different Species supporting
confidence: 60%
“…The skin has proved to be a good site for parasitological confirmation (Madeira et al, 2009), and it is an important indicator, considering that the transmission of infection occurs during the blood feeding of the insect vector. Furthermore, the material collected from the same place on the skin can be used to perform other diagnostic tests, as the three used in this study as reference standard (parasitological culture, HE, and IHC), with no need to increase the number of biological specimens collected from the animal (Xavier et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, Latif et al (2004) showed that Hyalomma anatolicum could be infected with a trypanosome described as T. theileri when feeding as nymphs on an infected calf and that T. theileri survived the moult and multiplied in the resulting unfed adult ticks. Another species with phylogenetic proximity to T. rhipicephalis is T. caninum isolated in axenic culture from the skin of domestic dogs captured in different states of Brazil, including Rio de Janeiro (Madeira et al 2009;Barros et al 2015). Although the vector of T. caninum is still unknown, it is possible that it is transmitted by ticks, which might validate the phylogenetic proximity of T. rhipicephalis to T. caninum.…”
Section: Parasitology Openmentioning
confidence: 99%